Legal Analysis of the Transfer of Land Use Rights into Industrial Areas - Manullang, Imelda Arthameisia; ., Taupiqqurrahman (UNIVERSITAS PAKUAN, 2025)
Abstract Land is an agrarian resource with strategic importance for national development and public welfare. One form of land tenure regulated under the Basic Agrarian Law is the Right to Cultivate. Economic growth and the rising demand for industrial land have driven the conversion of Right to Cultivate land into industrial areas. This study analyzes the process and legal consequences of such conversion under Indonesian law. Using a normative juridical method with statutory and literature approaches, the research finds that the process involves relinquishment of rights, spatial plan revision, fulfillment of Spatial Utilization Suitability, and issuance of an Industrial Estate Business License. Legally, this conversion may give rise to juridical implications concerning land-use changes, spatial conformity, and environmental management obligations. Land conversion policies must uphold the principles of land’s social function and sustainable development to ensure legal certainty and public welfare. Keyword : Right to Cultivate, Industrial Area, Legal Certainty.